APLIKASI MODEL HALL’S CARE, CURE, CORE DALAM MANAJEMEN PERAWATAN SKABIES PADA WARGA BINAAN PEMASYARAKATAN DI LAPAS KELAS 1A SEMARANG - Khoiriyah, Siti; Mustajab, Abdullah Azam; Andriany, Megah; Setyawati, Ari (Jurnal Ilmiah Kesehatan, 2022)
Purpose of this study is to apply the Hall's model in managing scabies care for inmates in the Class 1A Prison in Semarang. Scabies can attack anyone of all ages, races and socio-economic levels. Poverty conditions in developing countries contribute to the high pre:valence of scabies which is linked to low levels of hygiene, difficulty accessing water, and overcrowded housing. This condition certainly requires appropriate intervention to overcome the problem of scabies. Method for applying the core, cure, and care model to 10 WBP sufferers of scabies is to carry out nursing interventions including health education, environmental decontamination, and collaborative treatment. Results complexity of scabies care and treatment requires collaboration with various parties from WBP, health workers, and health cadres or curves. After the intervention, 8 (80%) WBP recovered from scabies, and 2 (20%) WBP scabies reduced. Conclusion Providing interventions such as health education, treatment and environmental decontamination resulted in a reduction in scabies rates.